MECHANICAL PROPERTIES OF PINEAPPLE LEAF FIBER/ EPOXY COMPOSITES WITH 0°/0°/0°/0° AND 0°/90°/0°/90° FIBER ORIENTATIONS - Arini Shafia Afkari; Randito Ananta Pratama; Ariadne Laksmidevi Juwono; Seto Roseno (Jurnal Sains Materi Indonesia, 2022)
MECHANICAL PROPERTIES OF PINEAPPLE LEAF FIBER/ EPOXY COMPOSITES WITH 0°/0°/0°/0° AND 0°/90°/0°/90° FIBER ORIENTATIONS. Pineapple leaf fiber can replace synthetic fiber because of its environmentally friendly and abundant availability in Indonesia. The purpose of this study was to obtain the mechanical properties of the pineapple leaf fiber/epoxy composite with 0°/0°/0°/0° and 0°/90°/0°/90° fiber orientations. Pineapple leaf fiber from Subang Indonesia was pre-treated through alkalization. The composites were fabricated by hand lay-up, followed by the vacuum bagging method. The results showed that the flexural properties of both composites were higher than the tensile properties of both composites. The flexural strength and modulus of 0°/0°/0°/0° composites were higher than those of 0°/90°/0°/90° composites, with the values of (109.57 ± 8.12) MPa and (7.08 ± 0.62) GPa respectively. Morphological observations using a Scanning Electron Microscope (SEM) showed that pineapple leaf fiber and epoxy had strong interfacial bonds and few voids. According to SNI 01-4449-2006 for fiberboard, pineapple leaf fiber/ epoxy composites with 0°/0°/0°/0° and 0°/90°/0°/90° fiber orientations were categorized as high-density fiberboard type T2 45, because both composites had a density higher than 0.84 g/cm3 and a flexural strength higher than 45 MPa.